The Influence of Work Environment and Culture on the Performance of Barru Regency Population and Civil Registration Service Employees - Putri; Zalkha Soraya; Muhammad Akib (Pustaka Digital Indonesia, 2024)
The aim of this research is to determine the influence of work environment and culture on the performance of Barru Regency Population and Civil Registration Service employees. The population in this study were all 62 employees who worked in the Barru district population and civil registration service. The type of research used in this research is quantitative. The data collection method uses a questionnaire. The data analysis technique used is Multiple Regression Analysis using statistical calculations through the statistical package for the social science (SPSS) application. The results of this research indicate that work environment variables have a significant effect on employee performance. This is shown by the calculated t value of 4.823 which is smaller than the t table of 2.000 and the significant value of 0.000 is greater than 0.05. Work culture has a significant effect on employee performance. This is shown by the calculated t value of 2.786 which is greater than the t table of 2.000 and the significant value of 0.007 is smaller than 0.05